Refleksi Kekuatan Diri sebagai Upaya Peningkatan Kesehatan Jiwa dan Harga Diri Remaja Korban Perundungan - Giri Widakdo; Aisyah Aisyah; Naryati Naryati; Slametiningsih Slametiningsih; Elli Hidayati; Rahayu Hanan Labibah; Oki Rizkia Ainurahma Diniar (Universitas Malahayati Lampung, 2026)
ABSTRACT Adolescence is a crucial transitional phase characterized by physical, cognitive, and psychosocial changes. Psychosocial issues, such as bullying, often trigger a decline in self-esteem, anxiety, and even depression among adolescents. This community service initiative aims to enhance the self-esteem and mental resilience of students at SMKN 39 Central Jakarta through an intervention involving the